Acclimation of Biochemical and Diffusive Components of Photosynthesis in Rice, Wheat, and Maize to Heat and Water Deficit: Implications for Modeling Photosynthesis - Perdomo, Juan A.; Carmo-Silva, Elizabete; Hermida-Carrera, Carmen; Flexas, Jaume; Galmés, Jeroni (Frontiers in Plant Science, 2016)
The impact of the combined effects of heat stress, increased vapor pressure deficit (VPD) and water deficit on the physiology of major crops needs to be better understood to help identifying the expected negative consequences of climate change and heat waves on global agricultural productivity. To address this issue, rice, wheat and maize plants were grown under control temperature (CT, 25°C, VPD 1.8 kPa), and a high temperature (HT, 38°C, VPD 3.5 kPa), both under well-watered (WW) and water deficit (WD) conditions. Gas-exchange measurements showed that, in general, WD conditions affected the leaf conductance to CO2, while growth at HT had a more marked effect on the biochemistry of photosynthesis. When combined, HT and WD had an additive effect in limiting photosynthesis. The negative impacts of the imposed treatments on the processes governing leaf gas-exchange were species-dependent. Wheat presented a higher sensitivity while rice and maize showed a higher acclimation potential to increased temperature. Rubisco and PEPC kinetic constants determined in vitro at 25°C and 38°C were used to estimate Vcmax, Jmax and Vpmax in the modeling of C3 and C4 photosynthesis. The results here obtained reiterate the need to use species-specific and temperature-specific values for Rubisco and PEPC kinetic constants for a precise parameterization of the photosynthetic response to changing environmental conditions in different crop species.